The Comparison of Factors to Join Streetwear Virtual Community - Dirgoaji, Chrisnanda Mukti; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2019)
Technological advances on the internet, especially social media, have created virtual communities, especially in the fashion world. Virtual community’s existence gives people convenience way to keep up with fashion to follow the community. This research aims to analyse the significant differences between the existence of virtual communities’ variables in social media. This research used an online questionnaire to collect data which measured by a Likert scale to 211 respondents using purposive sampling and convenience sampling. The collected data was then processed using SPSS software. From the results of data processing and analysis of the data, it was found that all collected data is valid and can be used for research. In this research, the One-Way ANOVA method was used to measure and analyse the significant differences the variables. The results of this research indicate that there is a significant difference between the factors of the virtual community, which are Extrinsic Motivation, Usability, Sociability, Emotional Trust and Perceived internet Skills to join the community. Hopefully, this research can be useful for the virtual community to increase their followers and understand which factors that has a significant difference.Keywords: Significant Difference, Social Media, Virtual Community